(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Sincethe post-World War II years when development becomes a focus of concern withinthe western social sciences literature, the concept itself and the perspectivesin which it has been cached have undergone a series of dramatic changes.Initially the concept was interchangeably used with ‘growth’ today, today, thetwo are clearly distinguished. Growth has more limited connotations and isgenerally delineated by such quantifiable indices as GNP or per capita income.Development on the other hand implies a kind of structure change in all aspectsof society. They means certain core processes of charge whereby a society orpart of is transformed to the economic sphere from subsistence production tomass production from predominance of primary sector to secondary and tertiarysector from use of animal and human power to inanimate power in production,distribution, transport and communication. In the social sphere it entails aprocess of high social differentiation and specialisation with respect toinstitutional structure and individual activities where role recruitments arebased on performance rather than on ascription. At the political level, itmeans diffusion of power to owidening groups of society while beingbeneficiaries of the political process and the source of legitimacy of thesovereign authority.